Simultaneous determination of isoflavones and resveratrols for adulteration detection of soybean and peanut oils by mixed-mode SPE LC–MS/MS. (1st June 2015) - Zhao, Xin; Ma, Fei; Li, Peiwu; Li, Guangming; Zhang, Liangxiao; Zhang, Qi; Zhang, Wen; Wang, Xiupin
Highlights: Mixed-mode SPE LC-MS/MS method was developed for isoflavones and resveratrols. The extraction procedure can be achieved in 15 min and  avoiding tedious steps. The method was simple and applicable to quantify analytes in lipid matrix. Characteristic components could assess adulteration and quality of vegetable oils. Abstract: To ensure authenticity of vegetable oils, isoflavones (genistein, genistin, daidzein and daidzin) and resveratrols ( cis -resveratrol and trans -resveratrol) were selected as the putative markers for adulteration of soybean and peanut oils. Firstly, mixed mode solid-phase extraction coupled with liquid chromatography tandem mass spectrometry (mixed-mode SPE LC–MS/MS) method was developed to analyze isoflavones and resveratrols in vegetable oils. The concentration of marker compounds in vegetable oils were 0.08–1.47 mg kg −1 for daidzein, ND-78.9 μg kg −1 for daidzin, 0.40–5.89 mg kg −1 for genistein, 1.2–114.9 μg kg −1 for genistin, 3.1–85.0 μg kg −1 for trans -resveratrol and 1.9–51.0 μg kg −1 for cis -resveratrol, which are compatible with the raw materials for oil press. Additionally, the applicability of this method has been successfully tested in thirteen vegetable oils from the market. Mixed-mode SPE LC–MS/MS method can simultaneously detect isoflavones and resveratrols in vegetable oils and assess adulteration and quality of soybean and peanut oils.